Pres Jonathan presents cassava bread to FEC (30Nov2011) - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2011)
Nigerian President Goodluck Jonathan presenting IITA-developed bread with 40% cassava flour content to the members of the FEC, hinting at new national policy on bread content. Video grab from NTA1 newscast on 30 November 2011.